Lithium and preventing chemotherapy-induced peripheral neuropathy in breast cancer patients: a placebo-controlled randomized clinical trial - S. Najafi (BMC, 2021)
Abstract Background Chemotherapy-induced peripheral neuropathy (CIPN) is a common adverse effect of some chemotherapy regimens. Lithium has been suggested for CIPN in some animal studies. We aimed to study lithium’s preventive effect on CIPN in breast cancer patients treated with taxanes and platinum-based medications. Method A double-blind placebo-controlled randomized clinical trial (RCT) was implemented on 36 breast cancer patients in two equal-size groups by block randomization. Participants in both groups consumed daily tablets, either placebo or lithium (300 mg), for 5 days in each course of chemotherapy. The tablets were prescribed 1 day before the start of chemotherapy. The electromyography (EMG) and nerve-conduction-velocity (NCV) tests were achieved before the first chemotherapy, 3 and 9 months after the treatment. The changes and signs or symptoms of CIPN, such as numbness, tingling, freezing, sensitivity to touch, muscle weakness, fibrillation, and knee and elbow reflex disorders, were recorded by examination. The trend of outcome changes was compared between two groups during the 9 months of study. Results In both groups, neurologic signs and symptoms were exacerbated during the first 3 months and improved up to the ninth month of study. Results showed significant changes of all EMG-NCV variables during the 9 months of research in each group (P < 0.001), but the interaction of time and group effect was not significant in none of those indices. All symptoms changed significantly over the study time (P < 0.001) without significant statistical difference between the two groups (P=0.352). No side effect was found during the study. Conclusion The study showed that 300 mg lithium prescription once daily for 5 days might not effectively prevent CIPN in breast cancer patients. Evaluation of lithium effect on CIPN on different cancers in future studies is suggested. Trial registration Iranian Registry of Clinical Trials IRCT20160813029327N10 .  Registration date: May 16, 2018.